Mitochondrial deacetylase Sirt3 plays an important role in donor T cell responses after experimental allogeneic hematopoietic transplantation - Toubai, Tomomi; Rossi, Corinne (The journal of immunology, 2018)
Allogeneic hematopoietic cell transplantation (allo-HCT) through its graft-versus-tumor (GVT) effects is a curative therapy against many hematological malignancies. However, GVT is linked to harmful graft-versus-host disease (GVHD) after allo-HCT. Both GVT and GVHD require allogeneic T cell responses, which is an energetically costly process that causes oxidative stress. Sirtuin 3 (SIRT3), a mitochondrial histone deacetylase (HDAC), plays an important role in cellular processes through inhibition of reactive oxygen species (ROS). Nonmitochondrial class of HDACs regulate T cell responses, but the role of mitochondrial HDACs, specifically SIRT3, on donor T cell responses after allo-HCT remains unknown. In this study, we report that SIRT3-deficient (SIRT3−/−) donor T cells cause reduced GVHD severity in multiple clinically relevant murine models. The GVHD protective effect of allogeneic SIRT3−/− T cells was associated with a reduction in their activation, reduced CXCR3 expression, and no significant impact on cytokine secretion or cytotoxic functions. Intriguingly, the GVHD protective effect of SIRT3−/− T cells was associated with a reduction in ROS production, which is contrary to the effect of SIRT3 deficiency on ROS production in other cells/tissues and likely a consequence of their deficient activation. Notably, the reduction in GVHD in the gastrointestinal tract was not associated with a substantial reduction in the GVT effect. Collectively, these data reveal that SIRT3 activity promotes allogeneic donor T cell responses and ROS production without altering T cell cytokine or cytolytic functions and identify SIRT3 as a novel target on donor T cells to improve outcomes after allo-HCT.